DESIGN OF FOOD PHOTOGRAPHY MEDIA AS A RECOMMENDATION FOR STREET FOOD IN BATAM USING IDI METHOD - Deli Deli; Eko Prastius (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Photography has become one of the technology development form in this digital era. One form of the photography is food photography. Food photography is one of business development that has a high standard of selling by using food as its media object. Food industry has actually experienced a quite significant growth, but everything changed when the world being infected by COVID-19. This phenomenon of pandemic is certainly has a bad impact on the small business sector such as street vendors. In this research, author designed a street food photography using the Research and Development method which refers to the IDI (define, develop, evaluate) instructional model. Street food often defined as ready to eat food that sold by street vendors in public place such as parks, field, and public street sidewalks. This food photography design was created based on data that had been collected by author at street vendors in Batam. Data is obtained from observations, interviews and market research. The output of this research is 27 digital image of street food photography which was edited by using Adobe Lightroom. The development of this street food photography is expected to help street vendors to increase their sales turnover during this post-pandemic COVID-19.